An Atypical 15q11.2 Microdeletion Not Involving SNORD116 Resulting in Prader–Willi Syndrome - Molly M. Crenshaw; Sharon L. Graw; Dobromir Slavov; Theresa A. Boyle; Daniel G. Piqué; Matthew Taylor; Peter Baker (Case Reports in Genetics)
Loss of expression of paternally imprinted genes in the 15q11.2-q13 chromosomal region leads to the neurodevelopmental disorder Prader–Willi Syndrome (PWS). The PWS critical region contains four paternally expressed protein-coding genes along with small nucleolar RNA (snoRNA) genes under the control of the SNURF-SNRPN promoter, including the SNORD116 snoRNA gene cluster that is implicated in the PWS disease etiology. A 5-7 Mb deletion, maternal uniparental disomy, or an imprinting defect of chromosome 15q affect multiple genes in the PWS critical region, causing PWS. However, the individual contributions of these genes to the PWS phenotype remain elusive. Reports of smaller, atypical deletions may refine the boundaries of the PWS critical region or suggest additional disease-causing mechanisms. We describe an adult female with a classic PWS phenotype due to a 78 kb microdeletion that includes only exons 2 and 3 of SNURF-SNRPN with apparently preserved expression of SNORD116.